Nippon : (Konkusei- Sha, 1972)
Nihon-Kokusei-Zue has been published for the past 35 years and has been received in this country with wider and wider acclaim with the passing of each year. " NIPPON" has been enthusiastically receiced in many foreign countries, not to mention the foreign residents, businessmen, members of the diplomatic corps and tourist here. Its comprehensive and easy-to-read statistical surveys provode a true and clear picture of the basic situation confronting the people of present-day Japan,...